'Pockets of efficiency' in a low capacity state: dealing with the COVID-19 pandemic in Romania. Issue 3 (3rd July 2021) - Dumitrescu, Lucian
ABSTRACT: The article brings forward the case of Romania's low capacity state and the troubles it has run into in its attempt to deal with the COVID-19 pandemic. In order to avoid essentialization, the article addresses the question of the public health system, which mirrors Romania's low capacity state. The article argues that, due to a dearth of resources, the public health system has had a hard time implementing the 'test, trace, isolate strategy'. States that have effectively implemented such a strategy have been successful in their attempt to curb the community spread of coronavirus. Also, the article seeks to demonstrate that even in a low capacity state, one may run into 'pockets of efficiency', that is, public institutions where quality management coexists with neopatrimonial practices. In order to illuminate the existence of such 'pockets of efficiency', the article makes a comparison between public hospitals turned into COVID-19 hotspots by poor management. And public hospitals where sound management has kept the SARS-CoV-2 virus at bay. Considering that informality usually takes precedence over formality in low capacity states, the article seeks to find an explanation for the occurrence of 'pockets of efficiency' in a prevalent neopatrimonial milieu.